Pengaruh Penerapan Sitem Informasi Akuntansi, Prtisipasi Penyusunan Anggaran, Pengawasan Fungsional, Komitmen Organisasi dan Budaya Organisasi terhadap Kinerja Instansi Pemerintah Daerah - Adinda Mutia; Alfiati Silfi; Meilda Wiguna (SYNERGY: Jurnal Bisnis dan Manajemen, 2023)
This research is an empirical study that aims to test and prove the effect of applying accounting information systems, budgeting participation, functional oversight, organizational commitment, and organizational culture on the performance of local government agencies. This research was conducted in 44 OPDs in Pekanbaru City. The data used is primary data with questionnaire data sources. The sample for this study was 108 respondents using the saturated sample method, but only 93 (86.11%) respondents who filled out the questionnaire completely and could be processed. The analytical tool used in this research is using the SPSS program. Based on the analysis and testing of the partial t test hypothesis, it can be concluded that for variables (1) Application of Accounting Information Systems, (2) Participation in Budgeting, (3) Functional Supervision, (4) Organizational Commitment, and (5) Organizational Culture Has a Significant Influence Against the Performance of Local Government Agencies.